2003
DOI: 10.1046/j.1365-2605.2003.00409.x
|View full text |Cite
|
Sign up to set email alerts
|

Seminal immunoreactive relaxin in domestic animals and its relationship to sperm motility as a possible index for predicting the fertilizing ability of sires

Abstract: Although immunoassayable relaxin has been detected in human and boar seminal plasma, there is no evidence suggesting the existence of immunoreactive relaxin in the seminal plasma of other domestic animals. The first objective of this study was to determine whether immunoreactive relaxin was present in the seminal plasma of bulls, rams and he-goats. In addition, the correlation of immunoreactive relaxin with sperm motility as an index for predicting the fertilizing ability of bull sires was investigated. Semen … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
34
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(39 citation statements)
references
References 25 publications
5
34
0
Order By: Relevance
“…This corroborates earlier reports, which found relaxin in sheep by using assays directed against porcine relaxin (20,28). These findings are in agreement with the current knowledge from sequencing and phylogenetic analysis; relaxin-2 and -3 are expressed in all mammals, whereas only primates possess relaxin-1 (46).…”
Section: Discussionsupporting
confidence: 93%
“…This corroborates earlier reports, which found relaxin in sheep by using assays directed against porcine relaxin (20,28). These findings are in agreement with the current knowledge from sequencing and phylogenetic analysis; relaxin-2 and -3 are expressed in all mammals, whereas only primates possess relaxin-1 (46).…”
Section: Discussionsupporting
confidence: 93%
“…This hormone has been found in human seminal plasma (Essig et al, 1982;Lessing et al, 1986) and it has been found that it exerts physiological effects on spermatozoon motility in certain species of domestic animals, such as bulls (Kohsaka et al, 2003). Miah et al (2006) showed that boar spermatozoa incubation with relaxin signifi cantly stimulates motility, the percentage of AR and glucose use.…”
Section: Relaxinmentioning
confidence: 99%
“…Initially, it was thought that the relaxin produced in the male reproductive tract would be released exclusively in the seminal fluid to influence sperm motility (Sasaki et al 2001, Kohsaka et al 2003, Sherwood 2004. However, studies with relaxin gene knockout animals (M1RKO) show that relaxin also plays a role in growth and development of the male reproductive system (Samuel et al 2003a).…”
Section: Introductionmentioning
confidence: 99%